VARIASI GENETIK PERMUDAAN CENDANA (Santalum album Linn.) PADA BEBERAPA FISIOGNOMI DI WANAGAMA I MENGGUNAKAN PENANDA ISOENZIM - , YULIAH; , Dr. Sapto Indrioko, S.Hut, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Sandalwood (Santalum album Linn) is one of Indonesian original species, categorized as vulnerable tree species to extinct. Efforts has been established since 1968 to cultivate sandalwood by developing ex-situ conservation, including in Wanagama I Education Forest, Gunung Kidul. Currently, its natural regeneration spreadly occurs almost in all compartments in Wanagama I. Based on the dominant vegetation composition, Wanagama I could be classified into physiognomy I (compartment 7), physiognomy II (compartment 16) dan physiognomy III (compartment 5). The aims of this research weree: 1) to know population genetic variation of sandalwood regeneration on 3 different physiognomies, 2) to recognize the changes of population genetic variation in different regeneration stages, and 3) to develop conservation strategy of sandalwood based on its genetic information. This research combined field and laboratory activities. Field activity has been conducted in three compartments at Wanagama I Gunung Kidul that were selected purposively based on their physiognomy status. Survey has been conducted to investigate the sandalwood natural regeneration in those compartments using transects and observational plots with size of 20 x 20 m. In each plot, young sandalwood leaves in different regeneration stages were taken as samples of genetic materials. They were analyzed in the laboratory using isoenzymes. Enzyme systems used were EST (Esterase), DIA (Diaphorase) and SHD (Shikimate Dehydrogenase). The research results showed that there were 5 polymorphics loci and 12 alleles in all sample compartments. The average number of allele per locus for all physiognomy was 2,47. The average number of effective alleles per locus was 1.6223. Moreover, the average number of expected heterozygosity in all physiognomy was 0,333. The tree stage of physiognomy III showed the lowest expected heterozygosity (HE= 0,2444), while the highest one was found in the seedling stage of physiognomy I (HE= 0,3894). Beside, the average number of fixation index is -0,0366. The highest positive number of fixation index was found in the tree stage of physiognomy III (0,4545), while the highest negative number of fixation index was found in the sapling stage of physiognomy I (-0,2329). This research also suggests formulating sandalwood conservation strategy based on genetic variation information by facilitating rare alleles in order to prevent extinction, enlarging population size, managing pollinator agencies, and maintaining the existence of certain birds which is helpful for spreading sandalwood seed. Approaching to local community was also an important genetic conservation effort especially to actively participate in planting and maintaining the sandalwood species.